An improved dispatchable wind turbine generator and dual-battery energy storage system to reduce battery capacity requirement - Li, Y.; Choi, San Shing; Vilathgamuwa, D.; Yao, D. (2016)
© 2016 IEEE. This paper examines an improved dual-battery energy storage scheme designed to achieve wind power dispatchability. The capacity of the battery energy storage system is greatly reduced by allowing direct power flow from wind turbine generator to the grid via a dc bus, as the two batteries interchange their charging and discharging roles at specific time. The method to determine the optimal capacity of the energy storage system is given, and is based on the characteristics of the battery and long-term wind power profile. Numerical examples show the validity of the proposed schemes.